2011
DOI: 10.1371/journal.pone.0025451
|View full text |Cite|
|
Sign up to set email alerts
|

Radiogenomic Mapping of Edema/Cellular Invasion MRI-Phenotypes in Glioblastoma Multiforme

Abstract: BackgroundDespite recent discoveries of new molecular targets and pathways, the search for an effective therapy for Glioblastoma Multiforme (GBM) continues. A newly emerged field, radiogenomics, links gene expression profiles with MRI phenotypes. MRI-FLAIR is a noninvasive diagnostic modality and was previously found to correlate with cellular invasion in GBM. Thus, our radiogenomic screen has the potential to reveal novel molecular determinants of invasion. Here, we present the first comprehensive radiogenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
198
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(202 citation statements)
references
References 49 publications
4
198
0
Order By: Relevance
“…9, These studies were published between 2007 and 2015. 8 studies used data from The Cancer Genome Atlas (TCGA) and/or The Cancer Imaging Archive (TCIA); 1,16,23,27,32,34,38,41 2 studies were multi-institutional; 9,19 and the remaining 17 studies used local institutional data. 15,17,18,[20][21][22][24][25][26]28,30,31,33,[35][36][37]39,40 26 out of 27 studies were retrospective in design.…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
See 1 more Smart Citation
“…9, These studies were published between 2007 and 2015. 8 studies used data from The Cancer Genome Atlas (TCGA) and/or The Cancer Imaging Archive (TCIA); 1,16,23,27,32,34,38,41 2 studies were multi-institutional; 9,19 and the remaining 17 studies used local institutional data. 15,17,18,[20][21][22][24][25][26]28,30,31,33,[35][36][37]39,40 26 out of 27 studies were retrospective in design.…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
“…8 (30%) studies used a validation data set to verify the association between imaging features and genomic data identified in the initial data set. 20,22,23,27,28,34,37,40 Six types of cancers were studied: glioblastoma multiforme (GBM)/high-grade glioma (n 5 14, 52%), non-small-cell lung cancer (NSCLC) (n 5 3, 11%), hepatocellular carcinoma (HCC) (n 5 3, 11%), breast cancer (n 5 5, 19%), clear-cell renal cell carcinoma (CCRCC) (n 5 1, 4%) and cervical cancer (n 5 1, 4%). The imaging modalities used included fluorine 18 fludeoxyglucose positron emission tomography (PET) (n 5 4, 15%), MRI [n 5 18 (including two perfusion MR), 67%] and CT [n 5 5 (including one perfusion CT), 19%].…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
“…2,3 In support of this hypothesis, region-specific brain tumor cells of origin have been identified in oligodendrogliomas, 4 medulloblastomas, 5 and ependymomas, 6 and compelling evidence has suggested that this is the case for IDH1 mutated gliomas. 7 Further, studies have identified clear links between radiologic features, including the volume and extent of edema and/or invasion 8 as well as contrast enhancement, 9 and -omic signatures. On the basis of these findings, we have constructed a set of radiographic atlases specifying the probability of tumor location and volumetric information for important demographic, -omic, and interventional phenotypes, with the goal of providing new insight into the possible niche locations of cells of origin in glioblastoma.…”
mentioning
confidence: 99%
“…If imaging findings can correlate with clinically useful molecular or genomic biomarkers, then a potential exists for improved tissue sample targeting, 8 clinical decision making, response monitoring, 16 and discovering and validating molecular targets. 17 For example, higher expression of a gene correlated with invasion in glioblastoma by MR imaging and was subsequently found to be a prognostic biomarker of survival. 17 However, imaging-to-genetic cor-…”
mentioning
confidence: 99%
“…17 For example, higher expression of a gene correlated with invasion in glioblastoma by MR imaging and was subsequently found to be a prognostic biomarker of survival. 17 However, imaging-to-genetic cor-…”
mentioning
confidence: 99%